Chinese Herbal Medicine (MaZiRenWan) Improves Bowel Movement in Functional Constipation Through Down-Regulating Oleamide - Huang, Tao; Zhao, Ling; Lin, Cheng-Yuan; Lu, Lin; Ning, Zi-Wan; Hu, Dong-Dong; Zhong, Linda L. D.; Yang, Zhi-Jun; Bian, Zhao-Xiang (Frontiers in Pharmacology, 2020)
In a prospective, randomized, three-arms, controlled clinical study, Chinese Herbal Medicine MaZiRenWan (MZRW, also known as Hemp Seed Pill) demonstrates comparable efficacy with Senna for functional constipation (FC) during an 8-week treatment period. Both MZRW and Senna are better than a placebo; relative to Senna and a placebo, MZRW displayed a more sustained effect during the 8-week follow-up period. The characteristic pharmacological mechanism responsible for this observation is still unclear. To explore this, we collected pre- and post-treatment serum samples of 85 FC patients from MZRW/Senna/placebo treatment groups for pharmacometabolomic analysis. An ultrahigh-performance liquid chromatography-mass spectrometer (UPLC-MS) was used for metabolic profiling and quantification. In vivo studies were conducted in constipated C57BL/6J mice to verify the effects and corresponding mechanism(s) of the action of MZRW. Pearson correlation analysis, paired t-test, one-way ANOVA analysis, χ2 test, and Student t-test were used to interpret the clinical and preclinical data. Changes in levels of circulating oleamide and its derivatives negatively correlate with improvement in complete spontaneous bowel movement (CSBM) in the MZRW group (Pearson r = -0.59, p = 0.00057). The same did not hold true for either Senna or placebo groups. Oleamide is a known regulator of intestinal motility. MZRW treatment resulted in reduced levels of circulating oleamide in FC patients. Experimental verification showed that MZRW attenuated oleamide-induced slow intestinal motility in mice. MZRW decreased oleamide levels in serum, ileum, and colon in normal mice, but increased expression of colonic fatty acid amide hydrolase (FAAH). In conclusion, MZRW improved bowel movement in FC by down-regulating oleamide, possibly by enhancing FAAH-mediated degradation. Our findings suggest a novel therapeutic strategy for FC.